THE EFFECT OF COMMUNICATION AND WORK STRESS ON EMPLOYEE PERFORMANCE AT PT. SINAR SOSRO TANJUNG MORAWA - Khomeiny Yunior; Manzilina Reji Pertiwi (Jurnal Ekonomi Bisnis Manajemen Prima, 2019)
ABSTRACTTHE EFFECT OF COMMUNICATION AND WORK STRESS ON EMPLOYEE PERFORMANCE AT PT. SINAR SOSRO TANJUNG MORAWAMANZILINA REJI PERTIWI(1)Major: AccoungingFaculty of Economy, University of Prima IndonesiaKHOMEINY YUNIOR(2)icom_yunior@yahoo.co.idOne determinant of a company progress is its human resources. A company or any business entity feels that the absence of qualified resources will lead tounachievable goal in the company. But it is often not realized, the company only makes employees or their resources as a means to achieve its goals rather than as individuals who have a need for recognition and awards. This study was conducted to investigate and examine the effect of communication and work stress on employee performance at PT. Sinar Sosro Morawa. The theory used include definition, the essence, the factors that affect the benefits and objectives, approaches and indicators of communication variables, the stress of work and performance. The research approach is quantitative while this type of research is descriptive quantitative research. The nature of research is descriptive explanatory. The population of the study were 238 employees. By using simple random sampling, 149 samples were obtained. The results showed that simultaneously or partially communications and job stress affect the performance of employees. The results of the test showed 15.8% of determination coefficient of variation of performance ondependent variable can be explained by the independent variable of communication and work stress. The conclusion of this study states that simultaneously and partially communication and work stress significantly affect the performance of employees at PT. Sinar Sosro Morawa.